Analysis of biochar with different pyrolysis temperatures used as filler in epoxy resin composites. (March 2019) - Giorcelli, Mauro; Savi, Patrizia; Khan, Aamer; Tagliaferro, Alberto
Abstract: Biocomposites are composite materials formed by a matrix and a filler derived from natural biomass. The use of biomasses and other biogenic wastes in composites represent an eco-friendly way to use these natural fillers. Biochar is a solid material generated by pyrolysis of biomasses. It is characterized by high carbon content, and for this reason it can be considered a possible substitute for more expensive and/or less environment friendly carbon fillers in composites. Biochars produced at different pyrolysis temperatures are investigated in this work (Miscanthus). They were characterized as produced (morphology, elemental analysis, graphitization grade, DC electrical conductivity) and subsequently used as fillers in epoxy resin. The complex permittivity of composites was then investigated. The aim of this work is to predict the final electrical properties of the composite by an evaluation of biochars characteristics. Results on biochar characterization, in particular DC electrical conductivity, are in agreement with the electrical performances on final composites.